Pelatihan Pembuatan Makanan Keripik Sebagai Ide Kewirausahaan Bagi Masyarakat Di Desa Bukit Selamat Kecamatan Besitang - Muammar Al-Qadri; Abdul Halim; Dedy Syafrizal; Intan Fadhilla; Khairunnisa (peduli riset dan pengabdian masyarakat, 2023)
The problem with this activity was that there was a complaint from one of the hamlet heads that there were difficult job opportunities in the village and a lack of insight into starting a business, not only in the village but also for the chip business in Bukit Selamat. The implementation of this activity, firstly, aims to add insight from tubers that can be utilized as an activity or business, where this training is easy to learn and much interested in becoming one of the relevant businesses and secondly, with this training the community be able to utilize and understand the importance of ideas to add to the main livelihood of the results of entrepreneurship in a sphere both social, individual, and also community. The results of the activity show that the implementation of the training on making food (chip) as an entrepreneurial idea has the main goal of expecting the community to take advantage of this entrepreneurial idea as one of the additional insights to make businesses such as to increase basic livelihoods and create jobs.